Coordinated variable-based guidance method and experimental verification for multi-UAVs - Zhong-nan TANG; Hong-bo XIN; Yu-jie WANG; Qing-yang CHEN; Peng WANG; Xi-xiang YANG (工程科学学报, 2022)
With the gradual establishment of regional cooperative air defense systems by the world’s military powers, the success rate of a single-aircraft penetration operation is greatly reduced, and the concept of many-to-one cooperative operation has been widely valued. As a new type of lethal aerial weapon, suicide unmanned aerial vehicles (UAVs) have played an important role in many local wars recently. Compared with traditional missiles, suicide UAVs can hover in a combat area for a long time, waiting for potential targets. Moreover, a suicide UAV cannot be easily detected via an early warning system and can approach targets covertly. Further, the manufacturing cost of a suicide UAV is low, and it can form a large-scale swarm for a surprise attack. Therefore, in the foreseeable future, a multi-UAV cooperative attack is likely to subvert existing combat styles. According to the operational characteristics and requirements of multi-UAV cooperative attacks, a general guidance scheme for the cooperative attack of multi-UAVs is proposed. Based on the theory that proportional navigation law has trajectory uniqueness under specific variable constraints, the guidance phase is divided into coordination and terminal phases by selecting coordinated variables. The improved Dubins method is used in the track control of the coordination phase to realize the space–time synchronous convergence of coordination variables. The 3D space guidance is decoupled into longitudinal- and lateral-plane guidance in the terminal phase, and the impact time of the swarm is consistent based on the proportional guidance with the same coefficient. A track segment control realizes the space–time cooperation of the swarm considering the target defense range constraint. Numerical simulation and actual flight test results show that the scheme has real-time online planning ability, can realize an omnidirectional saturation attack under the space–time cooperation of a large-scale UAV swarm, and has high impact time and space precision.